THE EFFECT OF THE PBL LEARNING MODEL BASED ON SCIENCE, TECHNOLOGY, ENGINEERING, MATHEMATICS (STEM) ON THE COGNITIVE ABILITIES OF JUNIOR HIGH SCHOOL STUDENTS 1 BASA AMPEK BALAI TAPAN - Sonia Chantika Sari; Rahmah Evita Putri (Department of Science Education, 2022)
The purpose of this study was to see the significant difference in mean scores on students' cognitive abilities between the control class given conventional learning and the experimental class given the STEM-based PBL learning model, and to see the effect of the STEM-based PBL learning model on the cognitive abilities of students in SMP Negeri 1 Basa Ampek Balai Tapan. This type of research is quasi-experimental (Quasi Experimental Research). The research design used was Non Equivalent Control Group Design. The population in this study were students of class VIII SMP Negeri 1 Basa Ampek Balai Tapan. The sample in this study was 30 people for each control and experimental class. The sampling technique used purposive sampling. In this study, there are two sample classes, namely the experimental class and the control class. The instrument used in this study was a multiple choice written test. The data analysis technique used is the similarity of two means to determine differences in students' cognitive abilities. The results showed an increase in cognitive abilities in the experimental class. This is evidenced by the average posttest score of the experimental class which is higher than the control class and is supported by the hypothesis test carried out by the t-test, namely tcount (3.85)> ttable (1.67) at the real level α = 0 , 05 where dk = 60. Thus H0 is rejected and Ha is accepted. This shows that there is a significant effect of STEM-based PBL learning models on students' cognitive abilities.